Averting a Moroccan Revolution: The monarchy's preemptive spatial tactics and the quest for stability - Amin Alsaden (Stiftung Wissenschaft und Politik (SWP), 2012)
Morocco is often seen as the exception to the "Arab Spring". The country's socio-political profile suggested that it was only a matter of time for the disgruntled masses to take to the streets and bring down another autocracy that has monopolised governance for decades and on whom the country's ills can be blamed. Contrary to expectations to date, however, Morocco' regime has survived the regional unrest, and its leadership seems to be as strong as ever. This is often explained with the promises of political reform that King Mohammed VI issued soon after regional uprisings started. This succinct narrative, albeit factual, does not accurately reflect the relationship between the resilient monarchy and the country at large. Other factors - particularly the regime's approach to the country's built environment, which encompasses the range of deliberately constructed physical structures: from inhabitable spaces to supporting infrastructure - can help explain the endurance of the inherited political status quo
Keywords: 320